Digital marketing during the COVID-19 pandemic: a case study of its adoption by furniture manufacturers in Malaysia - Ratnasingam, Jegatheswaran; Ab Latib, Hazirah; Ioras, Florin; Mariapan, Manohar; Lim, Choon Liat (North Carolina State University * College of Natural Resources, 2021)
Contemporary furniture marketing platforms that are based on furniture exhibitions, retail malls, and galleries were severely disrupted by the global COVID-19 pandemic. Therefore, this study was conducted to evaluate the extent to which digital marketing tools were adopted by furniture manufacturers in Malaysia. The effectiveness of digital marketing tools was assessed as an alternative furniture marketing medium by means of a questionnaire distributed to various furniture suppliers. The results of the questionnaire indicated that the onset on the COVID-19 pandemic accelerated the adoption of digital marketing among furniture manufacturers of all sizes. Larger manufacturers had the financial means to make greater investments into digital marketing to utilize it compared to the small and medium-sized enterprises (SMEs). Digital marketing by website, email, and social media were the most common mediums used by furniture manufacturers. As for social media applications, Facebook, Twitter, and Instagram were the common platforms used by furniture manufacturers. Although some furniture manufacturers were familiar with digital marketing, many were not using it effectively due to a lack of skilled workers with the ability to manage such digital marketing tools. Limited financial capital, especially among the SMEs, also made it difficult to enable the adoption of digital marketing.